(untitled) (Sciences & Technologie. C, Biotechnologies, 2015)
This work aims at evaluating the antimicrobial activity of rosemary extracts (EBr, EAcOEt and En-BuOH) on eight strains of bacteria and three fungal strains by agar diffusion method. The quantification of total polyphenols using the Folin-Ciocalteu method and of the flavonoids revealed the richness of the rosemary in polyphenols (195.45 ± 4.16 mg EAG/g of EBr). The analysis by HPLC revealed the presence of rutin and the catechin in the extracts rosemary. The results revealed that the extracts of rosemary are showed antibacterial activity against the whole tested Bacterial strains and The rosemary EAcOEt has been the most active extract and it has revealed an interesting antibacterial activity against the multi-resistant strain Entérobacter sp (ESBL+HLC). Only inhibition of Klebseila pneumonia strain have shown very significatif correlation between polyphenolic content of EBr of rosemary and antibacterial activity (R2 =0.992). The results of the antifungal activity showed the inefficiency of all the extracts against the fungal strains.